Oral Health Knowledge and Experience of Pediatricians and Pediatric Residents in Kuwait: A Nationwide Cross-Sectional Survey Study - Abrar Alanzi; Saleh Hajiah; Anfal Faridoun; Aisha Alterkait (Hindawi Limited, 2022)
Objective. To evaluate the knowledge level and practice of pediatricians and pediatric residents regarding children's oral health in Kuwait. Subjects and Methods. A nationwide cross-sectional survey was distributed to pediatricians and pediatric residents practicing in Kuwait. Data concerning demographic variables, knowledge on dental caries preventive measures, current anticipatory guidance, and experience with dental problems and oral care were collected using online and paper-based surveys. Results. A total of 230 completed the survey with a response rate of 50.1%. Most respondents (81%) had noticed dental caries in children more frequently. Two-thirds of respondents felt confident in detecting dental caries. However, more than two-thirds were unfamiliar with preventive dental practices and the management of dental trauma. Only 16.5% of the respondents got satisfactory knowledge score on the preventive measures questions, and nearly 51% got satisfactory knowledge on the recent anticipatory guidance questions. No significant correlations were found between gender or years of practice and knowledge scores. Respondents' confidence in detecting caries was significantly associated with the knowledge score of the anticipatory guidance (p=0.003). Conclusion. Dental caries is an oral problem commonly encountered by many pediatricians and pediatric residents in Kuwait. The majority has adequate knowledge of the current anticipatory guidance of oral health issues, but they have insufficient knowledge levels on oral preventative measures. Adequate education and training in oral health are highly recommended.